A new history of Southeast Asia - Ricklefs, M. C. (Merle Calvin) (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2010)
A new, comprehensive, one volume history of Southeast Asia that spans prehistory to the present. Ricklefs brings together colleagues at the National University of Singapore whose expertise covers the entire region, encompassing political, social, economic, religious, and cultural history. -- Back Cover.
Opening with an account of the ethnic groups and initial cultural and social structures of Southeast Asia, the book moves through the early'classical' states, the arrival of new global religions, and the impact of non-indigenous actors. The history of early modern states and their colonial successors is followed by analysis of World War II across the region. Offering a definitive account of decolonization and early post-colonial nation-building, the text then transports us to modern-day Southeast Asia, exploring its place in a world recovering from the financial crisis. -- Back Cover.
The distinguished author team provide an authoritative and accessible narrative, drawing upon the latest research and offering detailed guidance on further reading. A landmark contribution to the field, this is an essential text for scholars, students, and anyone interested in Southeast Asia. --Back Cover.
Includes bibliographical references and index.
Keywords: Southeast Asia -- History